Interfaces da natureza em Grande Sertão: Veredas - um olhar ecocrítico - Almeida, Maria do Socorro Pereira de (2014)
This research aims to study the work Grande Sertão: Veredas, by Guimarães Rosa, focusing its efforts in investigating how the nature is represented in the narrative context and the intertwined human-nature-society relation. As understood here, the research leans to a recent strand of literary criticism, the Ecocriticism, once the web of the environmental relations that interlace human and nature through the literary text is delineated by it. The Work presents discussions in the area of the fundaments of Ecocriticism through some scholars as Cherryll Glotfelty, Greg Gerrard and other authors linked to ASLE, plus some Brazilian researchers who have been dedicating themselves to this line of research. Also, we observed some works that bring ideas consonant with this perspective and that can be considered pioneers, especially some from the nineteenth century. We sought, as an epistemological propose of approach, the phenomenological perspective, from the ideas of Edmund Husserl and Merleau-Ponty, and the historical-sociocultural perspective, based in various scholars, for we consider these as relevant directions in the work studied. It is exposed the features of nature, ecology and environment that are contemporarily represented, in order to understand its present characteristics, given the typology of nature that are intrinsic to Rosa s work. A special focus is given to the backcountry trails to observe the symmetries and asymmetries between space and place, the objective and subjective representation of the backcountry area, how the power is characterized in that place, and how all this refers symbolically to the hinterland/world and the hinterland/man. Still within this perspective, we accompany the jagunços through the crossings of Sussuarão and the Sucruiú village. Meanwhile, we seek to understand the representation of the water in the work, since this element is, sometimes, essence and north of the narrative. Following the steps of the jagunços, we observe how is presented the man/animal relation in Riobaldo s narrative. Finally, we came closer to some characters intending to comprehend their sense of values and the actions expressed by them that, under a cautious eye, come to reveal itself. In this context, we also try to observe how these characters, throughout the narrative, can foster the Ecocriticism study.